Phylogenetic relationship based on flavonoids and its regions studies on selected Boesenbergia species in Sabah - Lam, Nyee Fan (2004)
Nine species of Boesenbergia and one of Zingiber, namely, Zingiber philipseae were screened using HPLC equipped with a reversephased analytical column. The flow rate was 0. 5mUmin and gradient elution with 0. 5% aqueous Formic acid: Acetonitrile from 99: 1 to 0: 100 ratio in 25 minutes with detection over a wavelength range 190nm to 500nm and specific detection at 280nm. Types of flavonoids were viewed from the online spectra of the crude extract of each peak. Each species contained a few flavonoid compounds ranging from two (Boesenbergia sp. 4) to seven (Boesenbergia pulchella var. attenuata). All the Boesenbergia species were found to contain flavonone/flavononol compounds. From the nine species of Boesenbergia, seven were found to contain flavone glycosides except Boesenbergia sp. 4 and Boesenbergia sp. 5. Only four species of Boesenbergia were found to contain isoflavone compounds. They were Boesenbergia sp. 1, Boesenbergia aurantiaca, Boesenbergia aurantiaca var. and Boesenbergia sp. 5. Meanwhile, the only species from Peninsular Malaysia, Boesenbergia rotunda, was found to contain cha/cone which was undetected in the Bornean species. An alignment was made of 19 ITS sequences of Boesenbergia species, plus five outgroup sequences. A total of 248 parsimony-informative positions were done. Tamijia flagel/aris was used to root the tree and the monophyletic Hedychium species is the sister group to the Boesenbergia (Bootstrap=100%). Phylogenetic analysis of the ITS region resulted in the generation of a single most parsimonious tree. With the complete data matrix of the region, including uninformative characters, the resulting tree had a length (L) of 162288 steps with the following fit measures: Consistency lndex=0. 6877, Retention lndex=0. 7045 and Rescaled Consistency Jndex=0.4845. The phylogenetic tree partially resolved the relationship among species within the genus Boesenbergia. The species have some branches with weak bootstrap support, showing that some ambiguity still exist in the placement of species. Two group of Boesenbergia appeared monophyletic (Bootstrap= 97%). The first group is monophy/etic supported by 70% bootstrap value (BOESENBERG/A I) and the second group constitued BOESENBERG/A GLADE II: Borneo clade I, Borneo clade II, Borneo clade Ill, Borneo clade IV and B. rotunda (Bootstrap=98%). The flavonoid and ITS region data gave congruent results in the groupings of the above.